Success Rate Of Artificial Insemination Using Honey In Tris-Egg Yolk Dilution In Peanut Goats - Bette, Yustiani Yuliana; Nalley, Wilmientje Marlene (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
Artificial Insemination (AI) is a technique used to improve the genetic quality and quality of livestock. This study aims to determine the success rate of Artificial Insemination using honey as a Tris-Egg Yolk diluent in peanut goats. Two PE male goats aged 2-3 years as semen sources and 18 peanut goats as acceptor females aged 1-3 years have already given birth and are showing an estrus cycle. Acceptor females were divided into two groups with two replications. group 1, insemination using Tris-KT diluent without honey and Group 2 with Tris-KT+Md diluent 0.75 v/w. The semen used for insemination was liquid semen with a dose of 0.2 ml / head with a concentration of 3.89 ± 0.46 x 109 cells / ml and viability not below 50%. Data were analyzed using the Chi square (X)² test to.determine the effect of treatment on the Non Return Rate (NRR) value parameters for 3 estrus cycles after AI and the Conception Rate (CR) value based on observations of 2 month pregnancy. The results showed that there was no real difference between treatments (P>0.05) in pregnancy rates with NRR and CR values of 77.78% (P1) and 88.88% (P2).